L-arginine vs. L-glutamine oral suspensions for radiation-induced oral mucositis: a triple-blind randomized trial - Fatma E. A. Hassanein; Christine Mikhail; Sarah Elkot; Asmaa Abou-Bakr (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Radiation-induced oral mucositis (RIOM) severely impacts patients with head and neck cancer (HNC) undergoing radiotherapy, often leading to pain and malnutrition. L-arginine and glutamine are immune-enhancing amino acids with potential benefits in wound healing and inflammation control. This study evaluated the efficacy of L-arginine versus L-glutamine oral suspensions in managing RIOM. Methods In this triple-blind, randomized controlled trial, 69 HNC patients with RIOM were allocated to three groups (n = 23 each): Group I (L-arginine 5 g + maltodextrin 5 g), Group II (glutamine 5 g + maltodextrin 5 g), or Group III (maltodextrin 10 g). Outcomes, assessed at weeks 2, 5, and 7 of radiotherapy, included the WHO oral mucositis scale, Pain Visual Analogue Scale (Pain-VAS), body mass index (BMI), and Oral Health Impact Profile (OHIP-14) questionnaire. Results By week 5, WHO scale scores differed significantly among groups (p < 0.001), with arginine and glutamine groups exhibiting lower mucositis severity than the maltodextrin group. Pain-VAS scores at weeks 5 and 7 were significantly lower in the arginine and glutamine groups compared to maltodextrin (p = 0.004 and p < 0.001, respectively). By 7th week of radiotherapy, BMI was significantly decreased in the maltodextrin group than in either the arginine (p = 0.028) or glutamine (p = 0.001) groups, indicative of treatment-mediated weight loss. In contrast, the BMI over time in the arginine (p = 0.87) and glutamine (p = 0.170) groups were almost constant. This indicates that compared to maltodextrin alone, both amino acid supplements prevented a decline in BMI during radiotherapy. OHIP-14 scores improved significantly in the arginine and glutamine groups at weeks 5 and 7 (p < 0.001), indicating better quality of life. Conclusions Both L-arginine and glutamine significantly reduced RIOM severity, pain, and weight loss compared to maltodextrin, while improving quality of life in patients with head and neck cancer. Although no statistically significant difference was found between the two, a higher proportion of patients receiving L-arginine achieved complete healing by week 7, suggesting a potential late advantage. These findings support the use of both amino acids as viable options for symptom management during radiotherapy. Trial registration ClinicalTrials.gov (NCT06764420), registered 08/01/2024.